COMPARISON OF OUTCOME OF CLOMIPHENE CITRATE ALONE AND IN COMBINATION WITH PIOGLITAZONE FOR INDUCTION OF OVULATION IN INFERTILE WOMEN WITH POLYCYSTIC OVARIAN SYNDROME (The Research of Medical Science Review, 2024)
Introduction: Polycystic ovarian syndrome (PCOS) is a common endocrine condition and a primary contributor to infertility in women of reproductive age. Clomiphene citrate (CC) serves as a primary intervention for ovulation induction; yet, its effectiveness may be constrained in certain cases.Objectives: To compare the outcome of ovulation induction in clomiphene citrate (CC) alone and combined treatment with CC and pioglitazone in terms of mean maximum follicle size among infertile women with PCOS.Material and Methods: This randomized controlled trial was conducted at the Gynecology and Obstetrics Department, DHQ Teaching Hospital Rawalpindi, from August 2024 to February 2025. A total of 274 married women with PCOS and infertility were enrolled and randomized into two groups: Group A (CC alone, n=137) and Group B (CC + pioglitazone, n=137). Ultrasonographic folliculometry was performed until mature follicles were detected. Inj. hCG (10,000 IU) was given intramuscularly when at least one follicle ≥18 mm was formed in either ovary. Mean maximum follicle size was recorded over three menstrual cycles. Data were analyzed using SPSS.Results: The mean maximum follicle size was significantly larger in Group B (21.48 ± 2.26 mm) compared to Group A (18.53 ± 3.31 mm, p<0.001). Subgroup analyses confirmed the superiority of the combined treatment across age, BMI, residential status, duration of marriage, and type of infertility.Conclusion: The combination of pioglitazone with CC markedly improves follicular development in infertile patients with PCOS. This combination provides a relatively economical and attainable treatment approach, especially advantageous for resource-constrained environments. Additional research is required to assess long-term effects and safety profiles.